The Influence of Digital Media FOMO in terms of Interpersonal Communication - Shabbir, Taha (Journal of Intelligent Communication, 2023)
The major purpose of this research is to explore how our interpersonal interactions are changed by social media. The primary purpose of this investigation is to determine whether or not the use of social media has an impact on the quality of education we get. The descriptive and mixed methods of study are the types of research that we have decided to do. Our family, our friends, our fellow employees, and our fitness (mental and physical) make up our variables. We decided on a sample size of one hundred and used both convenience sampling and questionnaires. In order to test our hypothesis, we utilized SPSS to analyses the data we collected. We found that 60% of our respondents used social media for 3-5 hours, and 46% of our respondents did not agree that social media had worsened their personal relationships. This indicates that social media has a much more positive effect on relationships than is commonly believed. In addition, we found that 60% of our respondents used social media on a daily basis.